The impact of the COVID-19 pandemic on the activities of small enterprises on the example of business customers of a manufacturing company = Wpływ pandemii COVID-19 na działalność małych przedsiębiorstw na przykładzie klientów biznesowych przedsiębiorstwa produkcyjnego - Danielak, Wiesław (Zielona Góra: Faculty of Economics and Management Press)
The aim of the article is to show the impact of the COVID-19 pandemic on the activities of small enterprises on the example of business customers of a manufacturing company. The article contains current issues and presents problems regarding the global pandemic caused by COVID-19, which started in March 2020.
Keywords: pandemic crisis; COVID-19; small company; kryzys pandemiczny; małe przedsiębiorstwo